Activity impairment, work productivity, health-related quality-of-life, and costs associated with uncomplicated urinary tract infection among females in Germany - Megan O’Brien; Alen Marijam; Fanny S. Mitrani-Gold; Laura Terry; Gavin Taylor-Stokes; Ashish V. Joshi (PLoS ONE, 2025)
Uncomplicated urinary tract infections (uUTIs) represent a sizable healthcare burden with a substantial negative impact on patients’ health-related quality-of-life (HRQoL). However, the HRQoL impact of uUTI from the patient perspective is under-represented in research. A cross-sectional online survey assessed activity impairment and work productivity, HRQoL, costs, and treatment satisfaction of female patients with uUTIs in the US; the current study applies this earlier methodology to Germany to provide a European perspective. We examined: activity impairment and work productivity using Activity Impairment Assessment (AIA), and Work Productivity and Activity Impairment (WPAI) questionnaires, respectively; HRQoL using a modified Short Form-36, and participants completed the treatment satisfaction questionnaire for medication. Participants (≥ 12 years) self-reported a uUTI treated with oral antibiotics in the last 60 days, had no evidence of complicated UTI, and were recruited via a consumer panel. In the patient (N = 200) survey, bladder pain (70%), dysuria (69%), and frequent urination (66%) were the most common uUTI symptoms reported. Activities frequently affected by uUTI were sexual activity (56%) and exercise (48%), resulting in an overall AIA score of 8.2 indicating that activities among patients were impaired ‘most of the time’ during their recent uUTI. Absenteeism was 29% (of a 40-hour work week); presenteeism, 34%; and overall work impairment, 41%. Indirect costs due to impact of uUTI were €7.62/hour/participant, representing a loss for the employer. The lowest HRQoL scores were for mental (44%) and physical components (43%); emotional and physical functioning scores were 71% and 70%, respectively. Mean direct costs of €20.10 for medical treatments and €11.30 for other treatment costs were reported. Overall, most participants were satisfied with the uUTI treatment (76% satisfaction score). Results demonstrate the patient-reported burden of uUTI for patients and employers, with activities and ability to work impacted, resulting in a notable indirect burden in Europe.